(untitled) (The Research of Medical Science Review, 2024)
Broiler meat is considered as a rich source of nutrients. Phytobiotics offer immense therapeutic potential and can provide broiler chickens with a natural protein-rich diet. The present study was conducted to analyze the effects of Moringa oleifera, Mentha piperita, and zingiber officinale on the growth performance of broiler chicks and their use as an alternate source of antibiotics. One day old, thirty broilers were purchased from the local hatchery Faisalabad and were divided into five treatments. T0 was fed with basal diet, T1 was fed with 2% Moringa leaf powder (MLP), T2 was fed with 2% peppermint leaf powder (PLP), T3 was fed with ginger root powder (GRP) and T4 was fed with 0.5ml Enrofloxacin per 2L drinking water. The growth performance was calculated by the percentage weight gain and absolute weight gain on the weekly basis. All data was analyzed by using one-way ANOVA. Maximum weight gain was showed in T1 treatment (63.72 ±60.99) fed with 2% Moringa leaf powder and minimum WG was observed in T2 treatment (50.312 ±54.89) fed with 2% Peppermint leaf powder. Maximum average weight gain was showed in T1 treatment (205.25) fed with 2% Moringa leaf powder and minimum Av WG was observed in T2 treatment (143.25) fed with 2% peppermint leaf powder. Maximum absolute weight gain was showed in T1 treatment (260.25) fed with 2% moringa leaf powder and minimum Absolute WG was observed in T2 treatment (240.6) fed with 2% Peppermint leaf powder. Maximum Specific growth rate was showed in T1 2% MLP (19.86) and minimum SGR was observed in T2 2% PLP (18.94). Maximum FCR rate was showed inT4 treatment (1.73) fed with Enrofloxacin and minimum FCR was observed in T1 2% MLP (1.32227).To check the antibacterial activity of these plants powder against E.coli bacteria, ELISA test was performed before and after treating the groups with phytobiotics and Enrofloxacin. All treatments showed positive ELISA test result after affecting them with E.coli bacteria. Phytobiotics and antibiotics treated groups showed negative ELISA test result. Maximum ratio of ELISA negative test result OD (Optical density) was observer in T1 (0.08) 2% MLP and minimum in T4 (0.021) fed with Enrofloxacin. Therefore, it was concluded that these phytobiotics works as natural growth promoters and also alternate of antibiotics.